The Impact Of Ownership Concentration On Real And Accrual-Based Earnings Management: Evidence From Jordan - Rami Najeeb Mohammad Alzu’bi; Nathasa Mazna Ramli (Fakulti Ekonomi dan Muamalat, Universiti Sains Islam Malaysia, 2024)
e-Proceedings of The 10th Islamic Banking, Accounting and Finance International Conference 2022 (iBAF2022): “Future-Proofing for Business Excellence Through Islamic Banking, Accounting and Finance”/ Editors: Norhaziah Nawai, Khairil Faizal Khairi, Suhaila Abdul Hamid, Muhamad Azrin Nazri, Nur Ainna Ramli, Sumaiyah Abd Aziz, Mohd Adha Ibrahim, Syadiyah Abdul Shukor. 13th-14th September 2022 (Virtual Conference) Organized by: Faculty of Economics and Muamalat, Universiti Sains Islam Malaysia